Between ordinary and extraordinary : the normativity of the singular case in art and law - Condello, Angela (Brill research perspectives. Art and law., 2018)
What is the relationship between the general, abstract norm and the singular, concrete case that sometimes affirms a parallel, contrasting, norm? The present essay engages with this question. The argument stems from an analysis of extraordinary singular cases that sometimes emerge, sometimes are?produced? or?promoted? as exemplary (for strategic reasons, like in law). In this essay Angela Condello argues that approaching normativity in art and law from the perspective of the singular case also illustrates the theoretical importance of interdisciplinary legal scholarship, since the singularity creates room for extra-legal values to emerge as legitimate demands, desires, and needs.